Groundwater Quality assessment in agriculture dominant watershed of Southern Sri Lanka (Case study in Polwatumodera river basin water shed-Weligama, Denipitiya) - Piyadasa, Ranjana U. K. (My University, 2007)
Extend and magnitude of groundwater pollution due to fertilizer use in the permeable sandy unconfined aquifers in Polwatumodera river basin water shed- in Southern Sri Lanka was studied during January to June 2006, recognized by heavy agricultural activities. The study area is located in latitudes and longitudes of 80 022’, 5097, and agriculture fields are in Welihinda, Meeruppe and Eluwawala. Sixty dug wells are selected both the well situated in cultivated and non cultivated lands. Continues monitoring was conducted with respect to Groundwater levels, Electrical conductivity (EC), Total dissolved solids (TDS). Fifteen wells were selected for total chemical analysis. . The study aimed to identify corrective and behavior of the groundwater quality changers in agricultural areas due to fertilizer, present nitrate concentration in the groundwater; present groundwater levels fluctuations and groundwater consumption of the region. Nitrate concentration had a significant appearance in cultivated and non cultivated areas. Nitrate concentration was very low in non cultivated areas and composed 0-2 mg/l. In the cultivated areas Nitrate level depended on the crop pattern and the atmospheric precipitation. During the some plant sessions Nitrate level was high and composed 16 mg/l